Mechanisms of cage noise generation in machine tool bearings - Takeshima, Kazuho; Mutoh, Keisuke; Imanishi, Kenji; Oshima, Shunichi (Frontiers in Mechanical Engineering, 2025)
Cage instability in ball bearings can lead to torque fluctuations and significant noise. In machine tool spindles, which require high rotational precision, outer ring-guided cages are often preferred over common ball-guided cages. While outer ring-guided cages suppress instability modes caused by sliding friction between the cage and balls, increased interaction between the cage and outer ring can introduce other instability modes, leading to noise. Despite the critical implications of these findings, prior research into this specific type of cage instability, incorporating both experimental and analytical perspectives, remains limited. Therefore, in this study, we utilized a high-speed camera system to conduct visualization tests on cage behavior in grease-lubricated angular contact ball bearings used in machine tools. Through detailed image-processing of the results, we identified specific behaviors associated with cage noise. To facilitate the optimal design of the cage to stabilize these behaviors, we developed a dynamic analysis model focusing on the friction between the cage and the outer ring under grease lubrication, considering fluid pressure effects. The validity of this model was confirmed through experiments at various rotational speeds. This analytical model enabled us to elucidate the underlying mechanisms driving cage instability. The insights gained from this research are expected to significantly enhance the fundamental understanding of cage design principles aimed at eliminating cage noise.